Exploring the role and influence of Chinese millennial students in the UK based on a new developed model regarding their involvement in families’ decision-making in the purchase of luxury goods - Zhang, Xixi (2017)
Due to dissatisfaction of domestic luxury industry, two- thirds of Chinese luxury spending happens overseas. In addition to purchasing luxury goods on their global journey，asking friends and family members who stay abroad to help them purchase luxuries becomes a tradition in China. As a growing number of Chinese millennials which is also a significant segment for luxury consumption among Chinese consumers studying in the UK, in addition to themselves, they also provide a more wealth segment like their parents and other family members to the UK’ luxury market. This study aims to examine how Chinese millennial students help and influence their families' purchase of luxury goods in the UK. Qualitative research, more specifically, the in-depth interview was utilised in the research in order to investigate abundant insights regarding the shopping experience, buying process and the relationship between student agents and perception. This study recruited 20 of Chinese people including ten Chinese millennials studying in the UK and their family members in China for comparing and contrasting their different views. The author developed a new model based on the Engel-Blackwell-Miniard model and the gathered data to demonstrate Chinese millennial students’ roles and functions in their family members’ buying process. In addition, the reverse socialisation regarding students and their parent in the main stages of process can be identified.